(untitled) (Research, Society and Development, 2023)
To develop a mathematical model for optimizing the Water Pumping System (SBA) of the 10th Sector located in the city of Belém, State of Pará, Brazil, to evaluate the influence of the variables that impact on the consumption of electric energy and prioritize energy efficiency actions. The methodology was divided into 7 stages. In Stage 1, the verification of the design, characteristics and arrangement of the motor and pump sets and the SBA hydraulic devices was carried out. In Step 2, preliminary criteria were defined to define the model’s input variables and their limits. In the third (Stage 3), the hydroenergetic evaluation of the factorial design tests was carried out, through computer simulations to determine the output variable (electricity consumption) in different SBA operation routines. Then (Step 4), the optimized model was developed to determine the optimal condition of the SBA. After this step, the developed model was evaluated and adjusted (Step 5). And, finally, the response surface methodology for SBA optimization (Step 6) and model validation (Step 7) were applied in order to verify its effectiveness. Based on the results, from the developed and validated model, it was possible to verify the best energy efficiency strategy in the SBA, in addition to quantifying the increase or reduction in the consumption of electric energy.